Izzivi in izkušnje, povezani z dejavnim razvojem zelenih površin v okrožju Józsefváros v Budimpešti - Kondor, Attila Csaba (Urbani izziv, 2008)
This article is an attempt to present the theoretical and practical backgrounds of a participative green space development in Hungary. The renewed green space, Mátyás square is located in District VIII of Budapest, known as Józsefváros. The neighbourhood of Mátyás square had a very negative image, neglected residential areas extended into the heart of the district suffered by different social problems. The local government of Józsefváros elaborated the so called Magdolna Quarter Programme, that contains the detailsof the social rehabilitation of surroundings of Mátyás square. In frameof this programme - co-financed by EU through GreenKeys Project - the square has been renewed, a collaborative and participative green space development has been fulfilled. The authors were engaged in this model programme, they attempt to summarize briefly the experiences of this unique project of Budapest. The local residents were successfully involved into the planning and the implementation of the project. The participation was considerably efficient, however the experience shows that a participative project may be shorter than the project leaders thought. As a result of this activities the Urban Green Space Strategy of Józsefváros and a computer program for monitoring of green spaces were compiled as well.
Keywords: Budapest; Budimpešta; prenova; prostorski razvoj; urbanistično planiranje; zelene površine